An experimental investigation on seawater SO2 scrubbing for marine application. Issue 4 (22nd November 2012) - Caiazzo, Giuseppe; Langella, Giuseppe; Miccio, Francesco; Scala, Fabrizio
<x xml:space="preserve">Abstract</x> A seawater spray scrubber was set up and tested with focus to desulfurization of marine engine exhaust gas. Experimental tests were carried out simulating typical exhaust conditions of a marine diesel engine burning heavy fuel oil and using real seawater. Different flue gas flow rates, seawater flow rates, and SO2 concentrations were tested. Liquid‐to‐gas ratios were in the range 1–10 × 10−3. A comparison between seawater and distilled water was also carried out to elucidate the effect of seawater alkalinity. In all conditions, the liquid phase was analyzed for alkalinity, pH, and sulfate content before and after the tests. Finally, the spray droplet size distribution was measured as a function of liquid flow rate. Experimental results indicated that seawater performed better than distilled water, by exploiting its inherent alkalinity. The desulfurization performance was improved by increasing the liquid flow rate and the gas residence time and by decreasing the SO2 concentration. SO2 capture efficiencies up to 93% were measured under the present operating conditions. The experimental data were further compared with calculations performed with an available model for SO2 absorption in fall‐down droplets within a simple plug‐flow reactor. Model calculations were carried out by using all parameters' values as measured in the present experimental campaign. Model results well fit the experimental data, even if a slight underestimation of the desulfurization efficiency is reported. The likely reasons are the assumed plug flow of gas as well as the neglected contribution to SO2 capture by water film falling at the wall. © 2012 American Institute of Chemical Engineers Environ Prog, 32: 1179–1186, 2013